PENGARUH METODE ROLE PLAYING TERHADAP PEMBELAJARAN DRAMA - Nurul Anggita; H. Rustam Efendy Rasyid; Aswadi Aswadi (Cakrawala Indonesia, 2019)
The Effect of Role Playing Method on Drama Learning. his study aims to determine the effect of the role playing method on drama learning in class XI MIPA.3 students of SMA Negeri 6 Sidrap 2018/2019. This study was quasi-experimental research with sample 32 students. Data collected through documentation and test techniques. The results of data analysis showed that the average of the experimental group was higher than control group (78,12 >73,75). This shows that the alternative hypothesis "There is an influence of the role playing method on the learning of drama class XI MIPA.3 students of SMA Negeri 6 Sidrap", was accepted. Therefore, the null hypothesis "There is no effect of the role playing method on the drama learning in class XI MIPA.3 students of SMA Negeri 6 Sidrap ", was rejected.